For the Fun of It: Harnessing Immediate Rewards to Increase Persistence in Long-Term Goals - Woolley, Kaitlin; Fishbach, Ayelet (Journal of Consumer Research, 2016)
Pursuing personal goals for delayed rewards (e.g., exercising to improve health) often provides consumers with immediate rewards (e.g., a fun workout) in addition to the delayed rewards they receive. With regard to health and academic goals, we find that attending to the immediate rewards of health and academic activities increases persistence in these activities to a greater extent than attending to delayed rewards, even though these activities are selected for the delayed rewards they provide. Specifically, bringing immediate rewards into activity choice—for example, having participants choose the most enjoyable rather than the most useful exercise or the tastier rather than healthier bag of carrots—increases persistence and consumption. Similarly, adding external immediate rewards to activity pursuit—for example, playing music in a high school classroom—increases persistence. Across these studies, immediate rewards are stronger predictors of activity persistence than delayed rewards. This research suggests that marketers and consumers can harness immediate rewards to increase persistence in long-term goals.